Self-medication in university students from the city of Rio Grande, Brazil - Corrêa da Silva Marília; Soares Maria Cristina; Muccillo-Baisch Ana (BMC, 2012)
Abstract Background Self-medication is the use of medication without prescription, orientation, or supervision of a physician or dentist. Self-medication might become a serious health problem. The purpose of this study was to identify the prevalence and factors associated with self-medication among first and last-year students enrolled in healthcare and non-healthcare programs. Methods A cross-sectional study was conducted at Universidade Federal do Rio Grande (FURG), state of Rio Grande do Sul, Brazil. Of 830 students in the sample, 95% answered the questionnaire - 789 students enrolled in 10 undergraduate programs. Mean age was 22 ± 6.17 years. The students answered a questionnaire covering socio-economic and demographic variables, use of medication, and medication knowledge. Information was collected on the conditions treated with medication, the medications used, and attitude towards self-medication. Results Of 789 students, 86.4% self-medicated (88.5% of 446 healthcare students). There were no significant differences in self-medication between healthcare and non-healthcare students, nor between first and last-year students. Bivariate and multivariate analyses showed a significant association between self-medication and having children (p = 0.01), having a home pharmacy (p < 0.001) and adequate medication knowledge (p = 0.01). The most frequently used active ingredients were acetaminophen (paracetamol), dipyrone, aspirin, phytotherapic compounds, and tea. Illicit drug use was significantly associated with self-medication in the multivariate analysis. Conclusion The fact that being a healthcare student was associated with higher medication knowledge, but not with less self-medication, suggests that medication knowledge might contribute to increase self-medication. This should be taken into account when designing educational interventions relating to self-medication.